Revision and phylogeny of the rare Priotomis Townes (Hymenoptera, Ichneumonidae, Cryptinae), with three new species and first description of the male - Tedesco, Anazélia M.; Aguiar, Alexandre P. (Zootaxa, 2011)
Priotomis vinhai Tedesco, sp. nov., from the restingas of southeastern Brazil, P. echyrus Tedesco, sp. nov., from Mexico and Costa Rica, and Priotomis flammatus Tedesco, sp. nov., from Panama and Brazil, are described and illustrated. The monophyly of the genus and the relationships of its species were cladistically tested using implied weighting, in a matrix with 22 species, including four species of Priotomis, and 92 external structural characters. Concavity constants (K) from 1 to 6 were tested. All analyses recovered Priotomis as monophyletic. A redescription of Priotomis is presented, combining the original definition with original information, expanding the limits of the genus. All results indicate P. vinhai, sp. nov. as the basal-most species of the genus; all results with K=2–5 recovered the apical clade P. rana + (P. echyrus, sp. nov. + P. flammatus, sp. nov.). An updated key to species is presented. Additional distribution records are provided, expanding the known range of Priotomis to 41º11’ latitude degrees, from Mexico to Argentina.